Pemodelan Habitat Potensial Tumbuhan Lebah Apis dorsata di Membalong, Belitung - Muhammad Basrowi; Ibnul Qayim; Rika Raffiudin (Jurnal Ilmu Pertanian Indonesia, 2022)
The forest becomes a habitat for honey bees to carry capacity for the supply of feed sources. Apis dorsata requires the availability of plants for supplying nectar and pollen. Traditional system in Belitung uses rafters for the efficiency of honey harvesting. Studies about preference habitats for bee forage become important to perform conservation of the honey bees. Therefore, the objective of this study was to (1) identify the composition, structure distribution patterns and vegetation profiles, (2) identify the area of the appropriate habitat model and environmental variables that influence the carrying capacity to provide bee forage of A. dorsata. Purposive sampling was used to analyze vegetation structure, distribution patterns, and vegetation profiles. The determination of the distribution of species is obtained from the Morishita index. We used MaxEnt for species distribution modeling to predict the potential plant habitat of bee plants. Our results showed that five most highest-importance plants. Myrtaceae is a family with dominant compositions and INP such as Melaleuca cajuputi, Tristaniopsis obovata, and Eugenia leptantha. The structure of other families such as Theaceae (Schima wallichii), and Clusiaceae (Calophyllum pulcherrimum), are the species that have the highest importance. The pattern of distribution of bee forage is clumped. The canopy cover around the honeycomb area tends to be relatively open. Based on the modeling habitat, categories with very appropriate for the presence of bee forage not spread throughout Membalong Regency with a percentage of the area (4.86%) and in the buffer zone (10.53%), environmental variables that influence the distribution are temperature seasonality, maximum temperature warmest month, slope, precipitation on warmest quarter and soil ph. Keywords: habitat modeling, rafter, spatial distribution, vegetation analysis, vegetation profiles